Stopping power of palladium for protons in the energy range 0.300-3.100 MeV - Miranda, P. A. (2013)
Fil: Rodríguez Cabello, Tabatha Pamela. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.